Research of the antioxidants content in plant raw materials – ingredients for polycomponent functional chips - O. V. Perfilova; Z. Yu. Rodina; K. V. Bryksina; A. S. Ilyinsky (Новые технологии)
The article discusses the possibility of using such plant raw materials as pumpkin varieties of Michurinskaya, Krasnaya Malyshka and hybrid Azhur medoviy F1, calendula flower powder, corn flour when designing new types of multicomponent chips ensuring the principle of resource saving due to the involvement of apple production pomace in the technological process juice. A comprehensive analysis of plant raw materials used in the production of chips was carried out for the total content of antioxidants, polyphenolic composition (flavonols, catechins, anthocyanins), the presence of ascorbic acid and beta-carotene. Among the varieties and hybrids of pumpkin, in terms of the total content of water-soluble antioxidants, Krasnaya Malyshka and Azhur Medoviy F1 stand out, then apple pomace, corn flour are ranked in increasing antioxidant value, and the leader here is calendula flower powder. The content of polyphenols in the hybrid Azhur medoviy F1 is higher than in the varieties of Michurinskaya and Krasnaya Malyshka by an average of 42%. The maximum content of ascorbic acid was found in Krasnaya Malyshka pumpkin, but at the same time this variety is inferior in beta-carotene content to two other varieties Michurinskaya and the hybrid Azhur medoviy F1 by 58 and 54%, respectively. Apple pomace can act as an additional source of ascorbic acid and flavonols, calendula flower powder – ascorbic acid, polyphenols and beta-carotene, and corn flour – flavonols, catechins and beta-carotene. All pumpkin varieties and hybrids studied in the work ensure that the finished multicomponent chips, taking into account the established recommended consumption rate – 30 g per day, contain functional ingredients – ascorbic acid, beta-carotene and flavonols at a level of more than 15% of the physiological consumption rate per day.